Microbial pattern of urinary catheterization infection at Wahidin Sudirohusodo Hospital - Muhammad Akmal Sukara; Nasir Djide; Nasrum Massi (Universitas Mataram, 2021)
Infectious disease still remains a serious problem in Indonesia and worldwide, it leads to use of uncontrollable anti-microbial treatment with cause to drug resistance. With unsupported condition for using a sensitivity test prior to antimicrobial treatment, a common guide for choosing an antimicrobial agent for infection of specific specimen is needed. The aims of this research is to determine the pattern of bacteria, more specific specimen is urine. This research was an observational Experimental consecutive sampling study, sample for this research were taken from inpatient room of Wahidin Sudirohusodo Hospital of Makassar during 2019-2020. The largest number of pathogenic bacteria that potentially becoming infection agent in inpatient room of Wahidin Sudirohusodo Makassar was E.coli, P.Aureginosa and Acinetobacter. Most of antimicrobial found in range of 61-70 years Old, and there was no significant relationship between sex and infections Sickness